Continuous Transesterification with Acidic Ionic Liquids as Homogeneous Catalysts. Issue 10 (10th September 2013) - Kuschnerow, J. C.; Titze‐Frech, K.; Schulz, P. S.; Wasserscheid, P.; Scholl, S.
Abstract Ionic liquids (ILs) are recyclable acid catalysts for transesterification reactions. In the present study, different acidic ILs were examined in this reaction, with special focus on their recyclability. Furthermore, the IL‐catalyzed transesterification reaction was realized in continuous operation. A miniplant reactor with technically representative design and operating characteristics was used for this study. The applied rig has a volume of 5 L and an external thermosyphon reboiler. The miniplant reactor can be operated in batch and in continuous mode. ILs functionalized with a sulfonic acid group were found to be the most suitable IL catalysts for the transesterification reactions under investigation. Using these ILs, reaction rates as high as for H2SO4 could be realized. Moreover, the IL catalyst was demonstrated to be active for at least 1000 h of operation time.